A hitherto unlocated Roman funerary stela from Abydos rediscovered. Issue 1 (January 2014) - Bommas, Martin
Rediscovery of the stela Abdalla 108, thought lost, in the William R. And Clarice V. Spurlock Museum at the University of Illinois